2017
DOI: 10.1103/physrevb.95.075307
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study on the B doping and B/P codoping of Si nanocrystals embedded in SiO2

Abstract: Doping silicon nanocrystals (Si NCs) embedded in silicon dioxide (SiO 2 ) with boron (B) and phosphorus (P) is a promising way of tuning the properties of Si NCs. Here we take advantage of density functional theory to investigate the dependence of the structural and electronic properties of Si NCs embedded in SiO 2 on the doping of B and P. The locations and energy-level schemes are examined for singularly B-doped or B/P-codoped Si NCs embedded in SiO 2 with a perfect or defective Si/SiO 2 interface at which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Such configuration, named 1c, results more energetically favored than the 5, 4, 3, and 2 configurations, confirming the idea that the formation of the P-B bond prevails with respect to other Due to the polar nature of the P-B bond, the above condition implies the formation of a static electric dipole radially directed and preferentially located at the Si-NC surface, which points toward the Si-NC center. Similar results have been obtained by Ni et al [221]. The high stability of the dipole direction is evidenced by considering a configuration in which the codopants are switched, a B-P pair, named 1i (see Fig.…”
Section: Codopingsupporting
confidence: 84%
See 1 more Smart Citation
“…Such configuration, named 1c, results more energetically favored than the 5, 4, 3, and 2 configurations, confirming the idea that the formation of the P-B bond prevails with respect to other Due to the polar nature of the P-B bond, the above condition implies the formation of a static electric dipole radially directed and preferentially located at the Si-NC surface, which points toward the Si-NC center. Similar results have been obtained by Ni et al [221]. The high stability of the dipole direction is evidenced by considering a configuration in which the codopants are switched, a B-P pair, named 1i (see Fig.…”
Section: Codopingsupporting
confidence: 84%
“…Carvalho et al [164,165] A different encapsulated Si-NC was obtained by Ni et al [220,221]. Starting from the H-terminated Si 71 H 84 , they replaced H atoms with oxygens, which were then outwardly bonded by adding Si atoms.…”
Section: Ab-initio Calculations Formation Energies and Electronic Prmentioning
confidence: 99%
“…First, the hollow SiO 2 nanospheres (HSiO 2 ) with ordered meso-aisles were synthesized by a spontaneous self-transformation method. , Then, the HSiO 2 and boric oxide were transferred into B-doped Si/SiO x according to a modified magnesiothermic reduction process. For B doping, the B atoms prefer to locate at the periphery of Si nanocrystals of the Si/SiO x interface. After a facile solvothermal approach and nitridation treatment, VN/Ni nanoparticles were uniformly anchored on the surface of B-Si/SiO x . Then, a thin layer of resorcinol–formaldehyde (RF) resin polymer coated the B-Si/SiO x @VN/Ni by one-step sol–gel polymerization of resorcinol and formaldehyde in the presence of CTAB .…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, both theoretical and experimental studies have revealed that the doping effects in Si NCs are quite complicated and different from their bulk counterpart. [6][7][8][9][10][11] It seems that the introduced impurities tend to locate at the interfacial region rather than the substitutional sites in the core of Si NCs. [12][13][14][15] Moreover, due to the novel doping behaviors, one can find some new and interesting phenomena, such as the sub-band light emission in phosphorous (P) doped and P/boron (B) co-doped Si NCs, [16] and localized surface plasmon resonance in B and P hyper-doped Si NCs.…”
Section: Introductionmentioning
confidence: 99%